A novel mouse model of SARS‐CoV‐2 induced neuroinflammation. (20th December 2022) - Biose, Ifechukwude Joachim; Narayanappa, Amruta; Gressett, Timothy E; Leist, Sarah R; Srivastava, Akhilesh; Ismael, Saifudeen; Kolls, Jay; Baric, Ralph S; Bix, Gregory J
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection may impact neurological function acutely or chronically, even in the absence of severe respiratory illness. Developing clinically relevant laboratory models to understand the neuropathogenesis of SARS‐CoV‐2 infection is an important step towards unravelling this neurologic consequence. We hypothesize that mouse adapted SARS‐CoV‐2 viral infection will induce neuroinflammation in immuno‐competent C57BL/6J (10 weeks old male) as well as immunodeficient RAG2 −/‐ (10 weeks old male) and BALB/c (1 year old female) mice. Method: All three mouse strains were inoculated intranasally with a dose of 1×10 3 PFU/mouse (50 µL) of either mock or the mouse‐adapted (MA)10 strain of SARS‐CoV‐2 (BEI resource, NR‐55329). Mice were euthanized on day 2, 3, 7, 15 or 30 post infection and brain samples processed for qRT‐PCR, immunofluorescence, and H&E analysis. Result: SARS‐CoV‐2 MA10 resulted in a significantly higher (p < 0.05) mRNA expression for chemokine ligand 2 (CCL2) and lower (p < 0.05) mRNA expression for the blood‐brain barrier component Claudin‐5 in RAG2 −/‐ and WT mice when compared to mock infection. Also, SARS‐CoV‐2 MA10 infection increased microglial expression in 1 year old female BALB/c mice after 2 days of infection, compared to mock infected group. At 30 days post infection, MA10 infected BALB/c mice had a higher perivascular lymphocyte cuffing in the brain. Conclusion: This study demonstrates that the mouse‐adapted MA10 strain of SARS‐CoV‐2 can induce a neuroinflammatory state in the brain and more so in immunodeficient and aging mouse models. These mouse models will enable the investigation of the long‐term neurological effects of SARS‐CoV‐2 infection.